Urbanicity and risk of first-episode psychosis: incidence study in Brazil. (December 2019) - Del-Ben, Cristina Marta; Shuhama, Rosana; Loureiro, Camila Marcelino; Ragazzi, Taciana Cristina Carvalho; Zanatta, Daniela Perocco; Tenan, Silvia Helena Galo; Ferreira Santos, Jair Lício; Louzada-Junior, Paulo; dos Santos, Antonio Carlos; Morgan, Craig; Menezes, Paulo Rossi
Abstract : We estimated the incidence of first-episode psychosis over a 3-year period in a Brazilian catchment area comprising the region's main city, Ribeirão Preto (1 425 306 persons-years at risk), and 25 other municipalities with a total of 1 646 556 persons-years at risk. The incidence rates were estimated and adjusted by gender and age, using the direct standardisation method to the world population as reference. The incidence of psychosis was higher in the younger groups, men, and among Black and minority ethnic Brazilians. Psychosis incidence was lower in Ribeirão Preto (16.69/100 000 person-years at risk; 95% CI 15.68–17.70) compared with the average incidence in the remaining municipalities (21.25/100 000 person-years at risk; 95% CI 20.20–22.31), which have lower population density, suggesting a distinct role for urbanicity in the incidence of first-episode psychosis in low- and middle-income countries.